Effect of heat treatment on phase transformation of niti shape memory alloy produced by metal injection moulding / Ros Atikah Abdul Kadir, NurAtira Sharir and Muhammad Hussain Ismail - Abdul Kadir, Ros Atikah; Sharir, NurAtira; Ismail, Muhammad Hussain (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
The NiTi alloy is widely known for its unique properties which are pseudoelastic and shape memory effect. These two unique properties are suitable for biomedical applications such as an implant, biomedical suture etc. Various methods are available to produce NiTi such as Metal Injection Molding (MIM), Vacuum Arc Melting (VAM), Additive Manufacturing (AM), etc. The most common method is MIM, where the specimen undergoes the process of mixing, injection moulding, debinding and sintering. Commonly after the sintering process, the sample is inhomogeneous due to the formation of secondary phases and impurity content. These impurities content can be reduced by applying heat treatment which improves the microstructure of NiTi. The objective of the study is to investigate the effect of heat treatment on the microstructure and phase transformation of NiTi. In this study, samples were fabricated with each 50.0at% and 50.8at% of NiTi composition by using MIM. An annealing heat treatment of 430˚C was applied to the heattreated samples for increasing the yield strength of NiTi. All heat-treated samples were subjected to Differential Scanning Calorimetry (DSC) test for analysing the phase transformation; X-Ray Diffraction (XRD) test for identifying the existence of any secondary phases; and Scanning Electron Microscopy (SEM) test for observing the change in the microstructure. The results indicated that upon heating through the annealing process, the secondary phase of martensite, which is known as NiTi (B19’) diffused and formed the austenite phase of NiTi (B2). Results from the DSC and SEM analyses showed that the formation of B2 is dominant after the heat treatment process